Revolution in the City of Heroes : a Memoir of the Battle that Sparked Indonesia's National Revolution - Padmodiwiryo, Suhario (Monash University Publishing, 2016)
The battle of Surabaya looms large in the history of Indonesia. Yet the story of this battle is not well known outside of that nation. Based on the diary of 24-year-old Indonesian medical student Suhario Padmodiwiryo, Revolution in the City of Heroes is an evocative first-hand account of the popular uprising in Surabaya. It vividly portrays the chaotic swirl of events and the heady emotion of young people ready to sacrifice their lives for independence, and is essential reading for Australians seeking to gain a better understanding of their increasingly important northern neighbour.